Aplicación de la nic 2 y su impacto en los resultados de los estados financieros de la corporación pasteur sd cantón Santo Domingo año 2019. - Cedeño Cedeño, Diana Katherine (2021)
The objective of IAS 2 is to provide guidelines for the accounting treatment of inventories so that they can be reasonably disclosed in the Financial Statements, therefore, this research work sought to evaluate, strengthen, improve, and apply the current regulations through the objectives set and thus contribute to the proper management of inventories in the Corporation Pasteur SD. The qualitative-quantitative methodology allowed addressing the problems of the researched subject, which demanded the application of inductive, deductive, historical-logical, and analytical methods, in order to evaluate and interpret the data obtained through direct observation, interviews and relevant bibliographic documentation to demonstrate the internal procedures established by the administration to comply with the regulations. Through this study it was identified that there are deficiencies in the knowledge for the analysis of the Net Realizable Value (NRV) as indicated by the International Accounting Standard; in addition, inventory controls are performed empirically and lack pre-established indicators that help with the periodic evaluation of inventory management. Finally, the results were socialized with the pertinent authorities so that they can take the preventive and corrective measures they deem appropriate, and indicators were established to improve the analysis of slow inventory turnover. Key words: IAS 2, Financial Statements, Internal Control.